COMPARISON OF YIELD PERFORMANCE OF SOYBEAN VARIETIES UNDER SEMI- ARID CONDITIONS - A. Ali; Z. Iqbal; M. E. Safdar; M. Ashraf; M. Aziz; M. Asif; M. Mubeen; I. R. Noorka; A. Rehman (Journal of Animal and Plant Sciences, 2013)
Selection of suitable cultivar for an agro-climatic zone is of prime concern for soybean growers. Moreover, identification of suitable plant traits showing maximum contribution to final seed yield is important for plant architects. To find out superior varieties and plants traits for semi-arid conditions of Pakistani Punjab, growth and yield performance of four soybean varieties viz., Rawal, Williams-82, SA-72-60, and PSC-60 was tested through field study. Experiment was laid out in randomized complete block design (RCBD). Soybean variety PSC-60 showed best performance as it gave significantly higher seed yield (697.3 kg ha-1), biomass (2008 kg ha-1) plant population (31 plants ha-1), plant height (27.43 cm), number of leaves plant-1 (25), number of pods plant-1 (16.3), number of seeds pod-1 (2.867) and number of seed plant-1 (32.87). Contrastingly, soybean variety Williams-82 was found to be inferior as it gave lowest value of these parameters. Seed yield showed a significant positive relationship with plant population (R2=0.865), plant height (R2=0.652), leaves per plant (R2 =0.637) and plant biomass (R2=0.793), number of pods per plant (R2 =0.681), number of seeds per pod (R2 =0.793) and number of seeds per plant (R2 =0.685) whereas non-significant negative relationship with 100 seed weight and harvest index. The strongest relationship of seed yield was seen with number of seeds pod-1 (b=500.9) followed by number of pods plant-1 and the weakest with plant biomass (b=0.277). Therefore these traits should be considered to be most important while selecting improved soybean genotypes under semi-arid conditions.
Keywords: soybean; varieties; seed yield; plant traits; regression; biomass